2020
DOI: 10.3892/mmr.2020.11026
|View full text |Cite
|
Sign up to set email alerts
|

β‑asarone modulates Beclin‑1, LC3 and p62 expression to attenuate Aβ40 and Aβ42 levels in APP/PS1 transgenic mice with Alzheimer's disease

Abstract: alzheimer's disease (ad) is a common neurodegenerative disease in the elderly population. autophagy is a well-known regulator of neurodegenerative diseases and β-asarone has been discovered to have certain neuropharmacological effects. Thus, the present study aimed to analyze the potential effects of β-asarone in ad and its possible mechanism of action in relation to autophagy. The present study investigated the effects of β-asarone on the number of senile plaques and amyloid β(aβ) 40 , aβ 42 , amyloid precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The decrease in Beclin-1 may be due to the elimination of Aβ 1-42 from cells due to β-asarone. When the cause of stress state was relieved, the expression of Beclin-1 tended to return to normal level ( Deng et al, 2020 ). The decreased levels of p62 and LC3-Ⅱ suggest that the number of autophagosomes decreased, indicating that β-asarone promoted the clearance of Aβ 1-42 by promoting autophagosome-lysosome fusion or autolysosomal degradation ( Barbero-Camps et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in Beclin-1 may be due to the elimination of Aβ 1-42 from cells due to β-asarone. When the cause of stress state was relieved, the expression of Beclin-1 tended to return to normal level ( Deng et al, 2020 ). The decreased levels of p62 and LC3-Ⅱ suggest that the number of autophagosomes decreased, indicating that β-asarone promoted the clearance of Aβ 1-42 by promoting autophagosome-lysosome fusion or autolysosomal degradation ( Barbero-Camps et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of Aβ-induced mitochondrial dysfunction and impaired mitophagy was obtained by overexpressing parkin [ 107 ], an ubiquitin ligase that will be described in the next subsection. Moreover, in this connection, autophagy inhibition has been proposed as a tool to attenuate Aβ toxicity and neurodegeneration in Alzheimer transgenic mice models [ 108 ].…”
Section: Neurojanus Role Of P62mentioning
confidence: 99%
“…A very recent study found that α-asarone potentially targets the Aβ and tau pathology pathways by inhibiting Aβ 42 aggregation, in addition to inhibiting tau phosphorylation, resulting in improved spatial learning memory in APP/presenilin-1 (PS1) transgenic mice [ 28 ] ( Figure 3 ). Another study demonstrated that treatment with β-asarone reduced the number of senile plaques and decreased Aβ 40 , Aβ 42 , and APP expression levels in the hippocampus of APP/PS1 transgenic mice [ 85 ]. Moreover, β-asarone displayed a significant therapeutic effect against toxic protein deposition and increased the expression of the presynaptic protein synapsin 1 (SYN1), which should remove toxic superoxide anion radicals produced in cells [ 114 ].…”
Section: Neuroprotective Effects Of α- and β-Asaronementioning
confidence: 99%